2015
DOI: 10.15252/embj.201490702
|View full text |Cite
|
Sign up to set email alerts
|

Short loop length and high thermal stability determine genomic instability induced by G‐quadruplex‐forming minisatellites

Abstract: G-quadruplexes (G4) are polymorphic four-stranded structures formed by certain G-rich nucleic acids, with various biological roles. However, structural features dictating their formation and/or function in vivo are unknown. In S. cerevisiae, the pathological persistency of G4 within the CEB1 minisatellite induces its rearrangement during leading-strand replication. We now show that several other G4-forming sequences remain stable. Extensive mutagenesis of the CEB25 minisatellite motif reveals that only variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
147
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(178 citation statements)
references
References 68 publications
18
147
0
1
Order By: Relevance
“…To assess whether var -gene-associated PQSs might have more recombinogenic properties than PQSs located elsewhere, we scored both groups for the criteria that were reported in the yeast model system to define particularly recombinogenic motifs [30]: loop lengths of only 1 or 2 nucleotides, total loop length ≤7 nucleotides, single pyrimidine rather than purine loops, and having the longest of the three loops in the central position rather than a flanking position (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To assess whether var -gene-associated PQSs might have more recombinogenic properties than PQSs located elsewhere, we scored both groups for the criteria that were reported in the yeast model system to define particularly recombinogenic motifs [30]: loop lengths of only 1 or 2 nucleotides, total loop length ≤7 nucleotides, single pyrimidine rather than purine loops, and having the longest of the three loops in the central position rather than a flanking position (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Different G4 structures have different stabilities in vitro and in a yeast model system it was recently shown that this relates to their ability to promote recombination in vivo. Highly stable G4s, which generally featured very small loops containing single pyrimidines rather than single purines, were particularly prone to cause recombination events [30]. The authors then went on to establish that such sequences were under-represented in several other genomes from Caenorhabditis elegans to human, indicating that their particular recombinogenic properties may be selected against during genome evolution [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting this view, incorporation of sequences predicted to form particularly stable G4s leads to genetic instability in yeast, suggesting that these G4 structures are not processed efficiently and pose blocks to replication (12). Indeed, several helicases have been shown to possess G4 disruption activity (13).…”
Section: ___________________________________mentioning
confidence: 99%